THE THE PRODUCTION OF CASSAVA FLOUR IN THE CAIOAZINHO COMMUNITY, ITAPIRANGA/AM - Marques, Adilio Teixeira; Fortes, Mírcia Ribeiro (Revista Verde Grande: Geografia e Interdisciplinaridade, 2023)
Manioc flour is a food that is part of the Amazonian culture, widely produced and consumed in the state of Amazonas. The production process of cassava flour is predominantly artisanal, through family labor, focused on the local people’s trade and family consumption, has become one of the main products that raise the income of riverside communities in the state. Given the cultural and economic importance of the region, this article aims to understand the productive arrangement of cassava flour in the community of Caioazinho, in the municipality of Itapiranga - Amazonas, in the year 2019, as well as show the traditional practices used in the production, the family arrangement and the way of life of the residents of this community. For the elaboration of the research, the methodology will follow the proposal of Libault (1971) that defines four steps for the Research Geographical: The help in collecting, analyzing, organizing and systematizing bibliographic/cartographic data. This research is justified because it intends to contribute to the production and dissemination of knowledge about the municipality of Itapiranga, drawing attention to this production of the primary sector.